2011
DOI: 10.1074/jbc.m111.230516
|View full text |Cite
|
Sign up to set email alerts
|

The Pentatricopeptide Repeat Protein OTP87 Is Essential for RNA Editing of nad7 and atp1 Transcripts in Arabidopsis Mitochondria

Abstract: In plant organelles, RNA editing is a post-transcriptional mechanism that converts specific cytidines to uridines in RNA of both mitochondria and plastids, altering the information encoded by the gene. The cytidine to be edited is determined by a cis-element surrounding the editing site that is specifically recognized and bound by a trans-acting factor. All the trans-acting editing factors identified so far in plant organelles are members of a large protein family, the pentatricopeptide repeat (PPR) proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 65 publications
2
68
0
Order By: Relevance
“…Plant site-specific editing factors belong to the PLS subfamily of the PPR protein family (14). Binding of the cis-element and the PPR-PLS trans-factor has been demonstrated in several instances (35)(36)(37). Recent reports have demonstrated that RIPs, another small class of proteins, are also plant organelle editing transfactors (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Plant site-specific editing factors belong to the PLS subfamily of the PPR protein family (14). Binding of the cis-element and the PPR-PLS trans-factor has been demonstrated in several instances (35)(36)(37). Recent reports have demonstrated that RIPs, another small class of proteins, are also plant organelle editing transfactors (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, OTP87, a PPR-E editing factor, was shown to be dual-targeted to mitochondria and chloroplasts; however, although mutation of OTP87 was shown to affect mitochondrial editing, no effect on chloroplast editing extent in the mutant was reported (29). RIP1 is among about 50 dual-targeted proteins in plants reported to date; 16 of these proteins are amino acyl-tRNA synthetases (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…CRR4, a PPR-E protein necessary for the editing of the plastid ndhD transcript, directly interacts with the transcript in the area surrounding the targeted C for editing (12). Two other PPR editing trans-factors, the Physcomitrella patens PpPPR_71 and A. thaliana OTP87, have been shown to bind the RNA sequence surrounding their target editing sites (29,51). However, the identity of all the proteins that act in conjunction with PPR proteins to convert C targets to U targets is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations